2002
DOI: 10.1038/sj.onc.1205291
|View full text |Cite
|
Sign up to set email alerts
|

Complex roles of tissue inhibitors of metalloproteinases in cancer

Abstract: Matrix metalloproteinases (MMPs) is tightly associated with extracellular matrix (ECM) turnover, which plays a very active role in tumor invasion and metastasis. Tissue inhibitors of metalloproteinases (TIMPs) plays a critical role in the homeostasis of ECM by regulating the activity of MMPs. TIMPs are well-known for their ability to inhibit MMP activity thereby inhibiting tumor growth and metastasis. However, many evidences suggest that TIMPs are multifunctional proteins, which regulate cell proliferation, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
333
2
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(350 citation statements)
references
References 92 publications
5
333
2
10
Order By: Relevance
“…If TIMPs inhibit MMPs in vivo, it should be expected that high levels of these inhibitors would prevent tumour progression and thus be related with good outcome in patients with cancer. However, TIMPs are multifunctional proteins that in addition to their MMPinhibitory effect also demonstrate distinct tumour-stimulatory functions (Jiang et al, 2002). Experimental studies have shown that TIMP-3 may show activity to inhibit angiogenesis and induce apoptosis (Ahonen et al, 1998;Spurbeck et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If TIMPs inhibit MMPs in vivo, it should be expected that high levels of these inhibitors would prevent tumour progression and thus be related with good outcome in patients with cancer. However, TIMPs are multifunctional proteins that in addition to their MMPinhibitory effect also demonstrate distinct tumour-stimulatory functions (Jiang et al, 2002). Experimental studies have shown that TIMP-3 may show activity to inhibit angiogenesis and induce apoptosis (Ahonen et al, 1998;Spurbeck et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases may also regulate cancer/related angiogenesis, both positively through their ability to mobilise or activate proangiogenic factors (Stetler-Stevenson, 1999) and negatively via generation of angiogenesis inhibitors, such as angiostatin and endostatin, cleaved from large protein precursors (Cornelius et al, 1998). In addition, it is now assumed that TIMPs are multifactorial proteins also involved in the induction of proliferation and the inhibition of apoptosis (Jiang et al, 2002;Wurtz et al, 2005).…”
mentioning
confidence: 99%
“…TIMPs-1, -2, -3, -4 reversibly inhibit MMPs in a 1:1 stoichiometric fashion (Sternlicht and Werb, 2001). The different TIMPs differ in tissue-specific expression and ability to inhibit various MMPs and their capacity to interact or not with pro-MMPs (Jiang et al, 2002;Sternlicht and Werb, 2001 …”
Section: Mmp Structure and Functionsmentioning
confidence: 99%
“…6 -10 Thus, it has been speculated that TIMP-1 may actually play a dual role in cancer progression and metastasis. 11 Several studies have demonstrated that tumor tissue levels of MMP mRNA and protein are significantly increased in various malignant diseases and that such MMP elevations are correlated with cancer cell invasion, metastasis and short patient survival. 12,13 In addition, many reports have described similar overexpression of TIMP-1 mRNA and protein in several cancer types.…”
mentioning
confidence: 99%